(untitled) (Molecular Medicine Communications, 2023)
Human Immunodeficiency Virus (HIV) and Hepatitis C Virus (HCV) are among major health issues that affect a large section of the world’s population. While HCV affects around 170 million people worldwide, HIV affects 3% of the global population, with 10 million HCV cases documented in Pakistan alone. Co-infection with HIV and HCV results in a variety of genotypic patterns, with significant global heterogeneity in the incidence of spontaneous resolution of hepatitis C and the distribution of HCV genotypes among co-infected individuals. Co-infection is usually transmitted by sexual contact, contaminated blood supplies, and mother-to-child transmission, with high-risk populations like intravenous drug users (IDUs), and men who have sex with men (MSM) having increased vulnerability. This study, conducted in Karachi, Pakistan, aimed to explore the predominant genotypes and viral load of HIV and HCV. The genetic features of the HIV Gag and HCV NS5b genes were examined using genotyping techniques and phylogenetic methodology. The study revealed that out of the 150 individuals examined, 70 were diagnosed with HIV alone, 55 with HCV only, and 25 had both HIV and HCV infections concurrently. Furthermore, genetic analysis demonstrated that HIV-1 subtype A1 was the predominant genotype, with subtype C closely following. In the case of HCV, genotype 3a was the most prevalent in both mono- and co-infected individuals. Notably, individuals with dual infections exhibited limited genotypic variability for each virus. In the case of HIV co-infection, there was an elevation in viral load, while HCV demonstrated lower viremia relative to mono-infection. In conclusion, the study revealed the predominance of HIV-1 subtype A1 and HCV genotype 3a, as well as an elevated level of HIV and a lowered level of HCV in co-infection.